THE INFLUENCE OF ELECTRONIC SERVICE QUALITY AND CLIENT FULFILLMENT IN ONLINE BUYING: Study of Go Food Consumer in Malang - Yogatama, Ahmad Nizar (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
This study aims to determine the e-service quality in the online food business. The population of this study is GoFood application users in Indonesia who have visited, purchased, or used the services provided by the GoFood online food application at least once in six months aged over 17 years, totaling 354 respondents. The sampling method used is non-probability sampling. This research uses SEM-PLS. The results of this study are three dimensions of e-service quality, namely GoFood application design, customer security or privacy and fulfillment affect overall e-service quality. However, customer service is not significantly related to e-service quality as a whole. e-service quality as a whole is statistically significantly related to customer behavior. Future research should consider different methodologies for similar products, namely GrabFood and ShopeeFood.